Clinical nursing mentors’ motivation, attitude, and practice for mentoring and factors associated with them - Yan Wang; Suzhen Hu; Jiali Yao; Yangmiao Pan; Junling Wang; Hua Wang (BMC Nursing, 2024)
Abstract Objective To investigate the motivation, attitude, and practice toward mentoring and related factors among clinical nursing mentors. Methods This cross-sectional study included clinical nursing mentors from 30 hospitals in Zhejiang Province between August and September 2023. Demographic information, motivation, attitude, and practice were collected through a self-administered questionnaire. Results A total of 495 valid questionnaires were collected, and most of the participants were 30–39 years old (68.7%). Average motivation, attitude, and practice scores were 29 [26, 32] (possible range: 8–40), 87 (82, 94) (possible range: 22–110), and 41 (38, 45) (possible range: 11–55), respectively. Correlation analyses showed that the motivation scores were positively correlated with attitude scores (r = 0.498, P < 0.001) and practice scores (r = 0.408, P = 0.001), while attitude scores were positively correlated with practice scores (r = 0.554, P < 0.001). Multivariate logistic regression showed that intermediate and senior nursing mentors (OR = 0.638, 95% CI: [0.426–0.956], P = 0.030) and different hospitals (OR = 1.627, 95% CI: [1.054–2.511], P = 0.028) were independently associated with motivation. The hospital’s frequency of psychological care was a significant factor associated with nursing mentoring motivation, attitude, and practice. Participation in training (OR = 2.908, 95% CI: [1.430, 5.913], P = 0.003) and lower frequency of job evaluation in hospital (“Often”: OR = 0.416, 95% CI: [0.244–0.709], P = 0.001 and “Sometimes”: OR = 0.346, 95% CI: [0.184–0.650], P = 0.001) were independently associated with practice. Conclusion Clinical nursing mentors had adequate motivation, positive attitude, and proactive practice towards mentoring and associated factors. Clinical nursing mentorship should be enhanced by prioritizing mentor training, fostering a supportive environment with consistent psychological care, and promoting structured mentorship activities.